South Africa's law and policy framework for the regulation of the Clean Development Mechanism / Humphris, D.F. - Humphris, Daniël Francois (North-West University, 2012)
The Clean Development Mechanism is a flexible mechanism originating from international law to serve as a climate change mitigation vehicle. Climate change is an environmental phenomenon that will affect the world in a dramatic way. South Africa does not stand oblivious to these changes and must play an active role in the global community. From a legal perspective, recent years have generally seen significant developments in the domestic environmental law framework of South Africa. In order to focus and meaningfully comment on the status quo of South Africa’s existing legal framework, this study will critically evaluate the law and policy framework facilitating the Clean Development Mechanism in South Africa and propose possible improvements on the current system. === Thesis (LL.M. (Environmental law))--North-West University, Potchefstroom Campus, 2012.